Investigating agr Quorum Sensing and Autoinducing Peptide Biosynthesis in Staphylococcus aureus - Blower, Isobel (2023)
Staphylococcus aureus is a high priority pathogen which has generated resistance to multiple antibiotics meaning it is difficult to treat. Due to this, novel treatments for S. aureus infections are being investigated including the development of virulence factor inhibitors. Inhibiting the virulence of the bacterium will assist immune clearance, reducing the need for exposure to bactericidal antibiotics which provide pressure for resistance to emerge. In S. aureus virulence is largely controlled by the agr quorum sensing (QS) system. This is a means of bacterial communication via the release and detection of a signal molecule autoinducing peptide (AIP).